Primary sarcoma of the heart – case report - Łasińska, Izabela; Załuska, Joanna; J. Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2010)
Primary sarcomas of the heart are extremely rare. They are often diagnosed at advanced stage or even first during autopsy, because the early symptoms are untypical and uncharacteristic (chest pain, tachycardia, arrhythmias, right-or left- side heart failure). Other symptoms of this kind of malignancy may be: weight loss, night sweats, or fever. Treatment of primary heart sarcomas involve complicated surgical resection combined with adjuvant therapy (radio-, chemotherapy or both). Many small clinical studies were aimed to analyze the efficacy of systemic treatments based on classical cytotoxic drugs, on novel targeted agents (monoclonal antibodies, tyrosine or serine-threonine kinase inhibitors). Some trials have also evaluated the efficacy of sequentially administrated cytotoxic drugs. In the following article we describe a case of a 52 year-old male patients diagnosed with primary malignant fibrohistiocytoma of the heart.